ANALISIS ASPEK LITERASI PADA BUKU TEKS PELAJARAN IPA KELAS VIII MATERI ZAT ADITIF & ZAT ADIKTIF - Amara Dewanti; Jejem Mujamil; Eka Ad'hiya (Jurnal Penelitian Pendidikan Kimia: Kajian Hasil Penelitian Pendidikan Kimia, 2022)
This study is aims to obtain information on aspects of scientific literacy in science textbooks for class VIII odd semester materials for additives & addictive substances. The research instrument used in this study consisted of aspects of scientific knowledge, aspects of scientific competences and aspects of the context of science. The results of the research in books A and B shown that of the three aspects of scientific literacy, the scientific knowledge aspect has an average percentage of 69.45%, the scientific competences aspect has an average percentage of 22.52%, and the science context aspect has an average percentage of 69.45%. the average percentage is 8.03%. In book A, the science knowledge aspect is 67.74%, the science competences aspect is 25.81% and the science context aspect is 6.45%. Meanwhile, in book B the scientific knowledge aspect is 71.15%, the scientific competences aspect is 19.23% and the science context aspect is 9.62%. This shows that book B contains more aspects of scientific knowledge and aspects of the context of science and book A contains more aspects of scientific competences.